PENGEMBANGAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PBL) BERBASIS KEARIFAN LOKAL UNTUK MEMPERSIAPKAN CALON PENDIDIK YANG BERBUDAYA - Nurfidianty Annafi; Sry Agustina (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2018)
Abstract. This study aims to development learning model Project Based Learning (PBL) based on local wisdom as well as testing the feasibility of the product and the level of effectiveness of learning devices developed. This research is a research development which adopt model of Dick & Carey which include preliminary stage, analysis, design, development, and testing. The research subjects are students of class A and B third year, Chemistry Education of STKIP Bima. Data collection are conducted through tests and non-tests that include interviews, observations, questionnaires, instrument validation and knowledge test questions. The result of this research can be concluded that learning model PBL based on local wisdom can be applied to student of third year that is prospective educator in developing learning device, learning model PBL based on local wisdom suitable for use in learning. Based on the validator's assessment, the learning model has fulfilled the content validity with Vaiken ≥ 7,6, and the assessment of the lecturer and the student with the category "Good". Learning using the model PBL based on local wisdom fffective to improve learning outcomes knowledge and attitudes of students. The average value of the students' experimental class is higher than the control class.Keywords: Development of learning model, project based learning, local wisdom